Wolfhart Pannenberg, Openness to the World, and the Sensus Divinitatis - Hollingsworth, Andrew (Irish theological quarterly, 2021)
One of the foundational concepts for Wolfhart Pannenberg’s theological anthropology is his notion of ‘openness to the world.’ Openness to the world, according to Pannenberg, is essential to human identity in that one’s identity is established in their openness to the world, to the other, and, ultimately, to God. I aim to bring Pannenberg’s openness to the world into dialogue with the concept of the sensus divinitatis as articulated by John Calvin and further developed by Alvin Plantinga. The question driving this paper is whether or not Pannenberg’s openness to the world can rightly be understood as the sensus divinitatis, and, if so, what might be some benefits of it. I conclude that Pannenberg’s understanding of openness to the world is a fruitful way of understanding the sensus divinitatis and a fruitful way of arguing for and explaining humanity’s innate knowledge of God.